Spectroscopic Characterization of Omeprazole and Its Salts - Vrbanec, Tomislav; Šket, Primož; Merzel, Franci; Smrkolj, Matej; Grdadolnik, Jože (Journal of Spectroscopy, 2017)
During drug development, it is important to have a suitable crystalline form of the active pharmaceutical ingredient (API). Mostly, the basic options originate in the form of free base, acid, or salt. Substances that are stable only within a certain pH range are a challenge for the formulation. For the prazoles, which are known to be sensitive to degradation in an acid environment, the formulation is stabilized with alkaline additives or with the application of API formulated as basic salts. Therefore, preparation and characterization of basic salts are needed to monitor any possible salinization of free molecules. We synthesized salts of omeprazole from the group of alkali metals (Li, Na, and K) and alkaline earth metals (Mg, Ca). The purpose of the presented work is to demonstrate the applicability of vibrational spectroscopy to discriminate between the OMP and OMP-salt molecules. For this reason, the physicochemical properties of 5 salts were probed using infrared and Raman spectroscopy, NMR, TG, DSC, and theoretical calculation of vibrational frequencies. We found out that vibrational spectroscopy serves as an applicable spectroscopic tool which enables an accurate, quick, and nondestructive way to determine the characteristic of OMP and its salts.